Dampak Konfersi IFRS Terhadao BUMN - Atiningsih, Suci (STIE Surakarta, 2012)
The purpose of this study is to determine the development of IFRS convergence to BUMN(Stated Government) in Indonesia. Type of research is a qualitative research study provides an overview of the actual implementation of IFRS in a company in relation to financial reporting. The results of the study. This study is expected to determine the development of IFRS convergence for BUMN( Stated Government) in Indonesia